2020
DOI: 10.1016/j.ejps.2020.105297
|View full text |Cite
|
Sign up to set email alerts
|

Combining biorelevant in vitro and in silico tools to investigate the in vivo performance of the amorphous solid dispersion formulation of etravirine in the fed state

Abstract: Combining biorelevant in vitro and in silico tools to investigate the in vivo performance of the amorphous solid dispersion formulation of etravirine in the fed state..

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Litou et al also simulated the plasma profiles of a drug with significant precipitation observed in an in vitro biorelevant dissolution testing (USP Apparatus II). In that study, a simple first order precipitation equation was assumed in a commercial in silico model (Simcyp).…”
Section: Orally Administered Dds Formulationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Litou et al also simulated the plasma profiles of a drug with significant precipitation observed in an in vitro biorelevant dissolution testing (USP Apparatus II). In that study, a simple first order precipitation equation was assumed in a commercial in silico model (Simcyp).…”
Section: Orally Administered Dds Formulationsmentioning
confidence: 99%
“…Furthermore, the effect of phase separation of the ASD formulations in the gastrointestinal fluid on drug permeation in the intestinal epithelium has also been discussed. 10 Litou et al 12 also simulated the plasma profiles of a drug with significant precipitation observed in an in vitro biorelevant dissolution testing (USP Apparatus II). In that study, a simple first order precipitation equation was assumed in a commercial in silico model (Simcyp).…”
Section: Orally Administered Dds Formulationsmentioning
confidence: 99%
“…Dissolution experiments in Level II biorelevant media simulating the fasted and / or the fed state have proven more useful compared to the equilibrium solubility of the pure unformulated drug substance for identifying the "effective" solubility, modelling the dissolution experiments and forecasting the in vivo performance of bio-enabling formulations. In particular, two case example formulations were tested i.e., a nanosized [23] formulation of aprepitant and an amorphous solid dispersion (ASD) [24] of etravirine and the conclusions derived were the following:…”
Section: Into Pbpk Modelsmentioning
confidence: 99%
“…ASDs have been widely used in formulating poorly soluble drugs, and currently, more than 30 commercially available medicines are formulated using the ASD technology. , For these oral dosage forms, dissolution is the prerequisite for satisfactory absorption in the gastrointestinal tract. , However, the dissolution mechanism of ASDs remains elusive, and the dissolution performance depends on many factors related to formulation design and dissolution conditions. Once in contact with dissolution media, the hydrated ASDs may undergo drug crystallization or amorphous–amorphous phase separation while the drug and polymer are dissolving. , At the same time, drug crystallization or liquid–liquid phase separation may also occur spontaneously in the dissolution media that is often time supersaturated .…”
Section: Introductionmentioning
confidence: 99%
“…1,2 For these oral dosage forms, dissolution is the prerequisite for satisfactory absorption in the gastrointestinal tract. 3,4 However, the dissolution mechanism of ASDs remains elusive, and the dissolution performance depends on many factors related to formulation design and dissolution conditions. Once in contact with dissolution media, the hydrated ASDs may undergo drug crystallization or amorphous−amorphous phase separation while the drug and polymer are dissolving.…”
Section: ■ Introductionmentioning
confidence: 99%